Aplikasi Teknologi Budidaya Buah Naga untuk Daerah Pesisir di Kelurahan Kalijaga, Kecamatan Harjamukti, Kota Cirebon - Sudarjat Sudarjat; Erni Suminar; Muhammad Abdilah Hasan Qanit; Syariful Mubarok (Universitas Mathla'ul Anwar Banten, 2019)
APPLICATION OF DRAGON FRUIT CULTIVATION TECHNOLOGY FOR COASTAL AREAS IN KALIJAGA VILLAGE, HARJAMUKTI DISTRICT, CIREBON CITY. Dragon fruit is one of the growing fruit commodities and is widely known in Indonesia. The distribution process has reached all of Indonesia. The development of dragon fruit in West Java itself is still said to be low, so it is necessary to increase or open a new area for the cultivation process which directly helps in terms of land and water conservation. In West Java alone, one location that has the potential to become a dragon fruit cultivation area is the City of Cirebon. Cirebon City is a strategic city that connects West Java and Central Java. However, the condition of the land in Cirebon is mostly unproductive. So it is necessary to find ways to increase the productivity of the land, namely through the application of technology to cultivate dragon fruit plants in coastal areas. To increase public awareness to reproduce agricultural land in the area, one of them is the process of mentoring the introduction of suitable types of plants grown in the area and appropriate cultivation technology for the area. The area that will be used as partners for this activity is Kalijaga Village, Kec. Harjamukti by involving two farmer groups, Sekar Maju, and Sidemung. The method that will be carried out in this assistance is the process of counseling, practice and making demonstration plots of dragon fruit planting that can be used as a learning tool in the area. From the results of the counseling, it was seen that the community's enthusiasm was high to want to know more about dragon fruit and how to cultivate dragon fruit in the area, so that dragon fruit in the area could develop.